The Influence of MGMP Activities and Active Participation on Social Studies Teacher Competence in Musi Rawas Regency - Cici Srilestari; Anik Widiastuti; Royhan Zahir Al-Muqsith (MASI Mandiri Edukasi, 2026)
This study examines the influence of the Inter-School Learning Community (MGMP) Social Studies activities and active teacher participation on improving the competence of social studies teachers in Musi Rawas Regency, amid the challenges of the Industrial Revolution 4.0 era, which demands strengthening teachers' professional competence. The purpose of the study was to test the partial and simultaneous influence of these two variables on teacher competence. Quantitative associative research uses multiple linear regression. The population comprised 120 junior high school social studies teachers who were members of the MGMP IPS Musi Rawas Regency. A sample of 92 respondents was selected through proportional random sampling using the Slovin formula. The instrument was a Likert-scale questionnaire (1-5), tested for validity and reliability, and analyzed using SPSS for prerequisite tests (normality, multicollinearity, heteroscedasticity) and hypothesis testing (t-test, F, R²). The results showed that MGMP activities had a significant effect (Sig. 0.039) and active participation (Sig. 0.001) partially on teacher competence, as well as simultaneously (Sig. F 0.000) with a contribution of 51.8 percent. The conclusion states that the synergy of MGMP activities and active teacher participation significantly improves the competence of social studies teachers, it is recommended to strengthen MGMP management and the culture of participation.